Association between exposure to polycyclic aromatic hydrocarbons and endometriosis: data from the NHANES 2001–2006 - Li Zhang; Xiaojun Yang (Frontiers in Public Health, 2024)
AimTo evaluate the association between urinary polycyclic aromatic hydrocarbon (PAH) metabolites and the risk of endometriosis.MethodsThis cross-sectional study obtained data on women aged 20–54 years from the National Health and Nutrition Examination Survey (NHANES) 2001–2006. The weighted multivariate logistic regression model was established to assess the association between the eight urinary PAH metabolites and the risk of endometriosis. In this multivariate analysis, the eight urinary PAH metabolites were adjusted with urinary creatinine, and were divided into three groups according to tertiles: Tertile 1, Tertile 2 and Tertile 3. To evaluate the overall association of mixed PAH metabolites with endometriosis, the Bayesian kernel machine regression (BKMR) model was applied.ResultsTotally 1,291 women were included, of which 90 (6.97%) had endometriosis and 1,201 (93.03%) did not have endometriosis. After adjusting for age, race, smoking, age at menarche, hysterectomy, ovary removed, female hormone use, and menopause, compared with the Tertile 1 group, the Tertile 2 and Tertile 3 groups of all PAH metabolites demonstrated no significant risk of endometriosis. A positive tendency was found between mixed PAH metabolites and endometriosis when all the metabolites were at their 60th percentile levels or above compared with their median levels. When all the other metabolites were fixed at their median levels, 1-hydroxynaphthalene was positively correlated with endometriosis. Potential interactions existed between 1-hydroxynaphthalene and 2-hydroxynaphthalene and between 2-hydroxyfluorene and 3-hydroxyfluorene.ConclusionNo significant association was found between individual PAH metabolites and endometriosis. A positive association existed between mixed PAH metabolites and the risk of endometriosis.